Knowledge and Self-Efficacy Assessment of Residents and Fellows Following Palliative Care Unit Rotation: A Pilot Study. (June 2019) - Burmann, Sven Niklas; Neukirchen, Martin; Ostgathe, Christoph; Beckmann, Mingo; Schwartz, Jacqueline; Scheer, Karin; Klco-Brosius, Stephanie; Hense, Joerg; Teufel, Martin; Tewes, Mitra
Background: In Germany, some units of specialized palliative care (SPC) offer a 6- to 12-month rotation for resident physicians (RPs) and fellows from different specialties. Objective: This pilot study aimed to evaluate feasibility of assessing palliative care knowledge (PCK) and palliative care self-efficacy (PCSE) using a paper-based questionnaire. Methods: Palliative care knowledge and PCSE were assessed by introducing a score, followed by a descriptive analysis (determination of frequency, mean, median, and range) using nonparametric tests (χ 2 test, Mann–Whitney U test). Results: We assessed 17 RPs following SPC rotation and 16 board-certified specialists (BCSs) who had no experience in SPC from 3 German comprehensive cancer centers. Resident physicians were predominantly enrolled in residency programs of hematology and oncology (n = 6), anesthesiology (n = 6), and psychosomatic medicine (n = 3). Resident physicians rotated between year 1 and 8 of residency. Fifteen RPs (88%) had elected this rotation and 72% preferred 12-month duration. The total PCK score of PCK was 27 (RPs) and 24 (BCSs; P = .002). Mean PCSE scores were 46 (RPs) and 39 (BCSs; P = .016). Of 71% of RPs, only 27% of BCSs knew how support of hospice service was initiated ( P = .004). Participants rated the items as comprehensible (n = 24; 73%), relevant (n = 25; 76%) and the questionnaire as adequately long (n = 23; 70%). Conclusion: An improved PCK and PCSE were observed in physicians who rotated through an SPC unit; this resulted in an increased tangibility of local palliative care and hospice services. The questionnaire was comprehensible, relevant in terms of content, and adequate in length for a prospective multicenter survey.